2022
DOI: 10.3390/molecules27092873
|View full text |Cite
|
Sign up to set email alerts
|

Computational-Based Discovery of the Anti-Cancer Activities of Pyrrole-Based Compounds Targeting the Colchicine-Binding Site of Tubulin

Abstract: Despite the tubulin-binding agents (TBAs) that are widely used in the clinic for cancer therapy, tumor resistance to TBAs (both inherited and acquired) significantly impairs their effectiveness, thereby decreasing overall survival (OS) and progression-free survival (PFS) rates, especially for the patients with metastatic, recurrent, and unresectable forms of the disease. Therefore, the development of novel effective drugs interfering with the microtubules’ dynamic state remains a big challenge in current oncol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 64 publications
(63 reference statements)
1
3
0
Order By: Relevance
“…Other studies have shown a strong link between the antitumor effect of PTX-loaded polymeric nanocarrier and immunological responses, such as splenocyte growth and cytokine production. These results were in line with those of those other studies [90][91][92][93][94][95][96][97][98][99].…”
Section: Measurement Of Lymphocyte Proliferation Index Following Trea...supporting
confidence: 93%
See 1 more Smart Citation
“…Other studies have shown a strong link between the antitumor effect of PTX-loaded polymeric nanocarrier and immunological responses, such as splenocyte growth and cytokine production. These results were in line with those of those other studies [90][91][92][93][94][95][96][97][98][99].…”
Section: Measurement Of Lymphocyte Proliferation Index Following Trea...supporting
confidence: 93%
“…Apoptosis was triggered in tumor cells by the protein PTX, which worked by inhibiting cell division [99] and stabilizing the microtubule assembly through noncovalent interactions with the cytoskeleton. Wang…”
Section: Apoptosis Assaysmentioning
confidence: 99%
“…Female BALB/c mice (6-8 weeks old, 20-25 g in weight) were obtained from the animal house of the Faculty of Veterinary Medicine Al-Qasim Green University. They were housed in a conventional animal facility under standard laboratory conditions 53 .…”
Section: Vibrating Sample Magnetometer (Vsm)mentioning
confidence: 99%
“…19 Similarly, Abdelmaoujoud Taia and colleagues have synthesized new heterocycles, 1,2,3-triazoles, with anticorrosive activity, particularly for iron in acid solutions. 20 Moreover, heterocyclic pyrrole compounds, characterized by a ve-membered ring comprising four adjacent carbon atoms and one nitrogen atom, have recently been prepared by Sergei Boichuk et al 21 These products have found wide therapeutic applications 21,22 due to their diverse biological properties, 23 including antimicrobial 24 and anticancer activities. 25 Many pyrrole-based compounds are also widely used as anticorrosion agents to combat the degradation of various metallic materials, such as copper, iron, and aluminum, in corrosive environments.…”
Section: Introductionmentioning
confidence: 99%